Jasper fellowship award for best research study was awarded to Dr. Rene Somera - Somera, Rene (Animo Repository, 1999)
The Southeast Asian Ministers of Education Organization (SEAMEO) awarded Dr. Rene Somera, a Behavioral Sciences faculty and SDRC research associate of DLSU-Manila, the prestigious 1999 SEAMEO - Jasper Fellowship Award for Best Research Study. He received his award at the opening ceremony of the 22nd SEAMEO High Officials Meeting on November 24 in Bangkok.